M-LAT Acceptance and Decision-Making in Chongqing Secondary Schools: Urban-Rural Perspectives - Wang, Qian; Aida Hanim A. Hamid (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Mobile-accessible Learning Analytics Technology (M-LAT) offers valuable tools for datadriven educational decision-making, yet its acceptance varies across educational contexts. This study examines factors influencing M-LAT acceptance among secondary school teachers in Chongqing, China, and investigates its relationship with teaching decision-making. Data collected from 341 teachers (197 urban, 144 rural) revealed moderately high overall M-LAT acceptance (M = 3.68, SD = 0.79), with significant urban-rural differences. Structural equation modelling identified associations between M-LAT acceptance and professional development (β = 0.624), administrative support (β = 0.581), and mobile technology infrastructure (β = 0.537). M-LAT utilisation correlated with teaching decision-making efficacy (r = 0.578), with a stronger relationship among urban teachers (r = 0.612) than rural counterparts (r = 0.524). These findings highlight an urban-rural digital divide and provide evidence for enhancing mobile learning analytics implementation in secondary education.